Implementasi Model Pembelajaran Aktif Berbasis Kolaboratif untuk Meningkatkan Pemahaman Konseptual Siswa - Rahmi Putri; Marwah Hidayah; Gusmaneli Gusmaneli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the implementation of an active learning model based on collaboration to improve students’ conceptual understanding in Islamic Religious Education (PAI). The background of this research stems from the low level of student engagement in the learning process, which has resulted in less optimal understanding of religious concepts. The research employed a qualitative approach with a classroom action research (CAR) design conducted in two cycles. The subjects were eleventh-grade students at a senior high school in City X. Data were collected through observation, interviews, and conceptual understanding tests. The findings revealed that the implementation of the collaborative active learning model increased students’ participation in learning activities, fostered critical thinking skills, and enhanced their conceptual understanding of Islamic Education materials. Through group discussions, problem-solving activities, and reflection sessions, students became more cognitively and affectively engaged in the learning process. Therefore, the collaborative active learning model can serve as an effective alternative strategy to improve both the process and outcomes of Islamic Religious Education learning.